Formative Research to Explore Reasons for Low Use of a Non-profit Community Grocery Store and to Develop Potential Solutions (P13-007-19). (13th June 2019) - Daniel, Leena; Harper, Kaitlyn; Trujillo, Antonio; Poirier, Lisa; Gunen, Bengucan; Ali, Shahmir; Orta-Alemán, Dania; Santiago, Celina; Gu, Yuxuan; Xu, Yvonne; Gittelsohn, Joel
Abstract: Objectives: Salvation Army opened its first non-profit, retail food store, DMG Foods, on March 2018, in Baltimore, MD. DMG Foods aims to have the lowest food prices in the neighborhood and make healthful options affordable to low-income households; currently, however, the store's reach is limited with only 100–150 customers daily, with an average transaction of $14. This study aims to determine reasons for low use of DMG Foods and produce potential solutions that will improve consumer purchasing behavior. Methods: Mixed-methods formative research was conducted at DMG Foods. In-depth interviews were conducted with store staff ( n  = 6), wholesalers ( n  = 2), store users ( n  = 8), and store non-users ( n  = 8). Interviews were centered on store stocking, sales, marketing efforts, consumer behavior, perceptions regarding price of food, consumer attitudes toward the Salvation Army and the DMG Foods brand, the nutritional quality of the available foods, and the convenience of shopping at DMG Foods. Direct observations of store operations ( n  = 10) and a short demographic survey of store users ( n  = 100) were also conducted. All in-depth interviews were coded and analyzed using the software ATLAS.ti v.4.2 (Berlin). Results: Strategies developed include social marketing strategies to target specific audience segments, pricing manipulation to enhance healthier food choices, and adjustments to store and stocking logistics. Impacts will be assessed in terms of change in diet, food purchasing, total customers, and average purchase amount. Conclusions: The results of this study will be used to identify solutions and strategies that promote increased utilization of non-profit grocery stores to improve diet quality in low-income communities. Findings will provide Salvation Army with a blueprint for scaling up and developing a series of similar non-profit food retailers throughout the USA. Funding Sources: Johns Hopkins Department of International Health.